Coupling of parts accelerating structures RFQ and DTL in one resonator prestripping section the heavy ion linear accelerator MILAC - Bomko, V.O.; Zajtsev, B.V.; Kobets, A.P.; Pavlii, K.V.; Panov, V.V. (Вопросы атомной науки и техники, 2014)
New pre-stripping section (PSS-20) consists of two parts with diverse accelerating structures. On an initial part of acceleration of ions from 6 up to 150 keV/nucl. high capture in process of acceleration of the injected ions is provided interdigital (IH) accelerating structure with Radio-Frequency Quadrupole (RFQ) focusing. On the second part of acceleration of ions from 150 keV/nucl. up to 1 MeV/nucl. the highest rate of acceleration is created interdigital (IH) accelerating structure DTL. The problem of diverse accelerating structures combination in one resonator is set. Новая предобдирочная секция ПОС-20 состоит из двух участков с разнородными ускоряющими структурами. На начальном участке ускорения ионов от 6 до 150 кэВ/нукл. высокий захват в процесс ускорения обеспечивает встречно-штыревая ускоряющая структура с RFQ. На втором участке ускорения ионов от 150 кэВ/нукл. до 1 МэВ/нукл. высокий темп ускорения создаёт встречно-штыревая ускоряющая структура DTL. Поставлена задача совмещения таких разнородных ускоряющих структур в одном резонаторе. Нова передобдиркова секція ПОС-20 складається із двох ділянок з різнорідними прискорюючими струк-турами. На початковій ділянці прискорення іонів від 6 до 150 кеВ/нукл. високе захоплення в процес прискорення забезпечує зустрічно-штирьова прискорююча структура з RFQ. На другій ділянці прискорення іонів від 150 кеВ/нукл. до 1 МеВ/нукл. високий темп прискорення створює зустрічно-штирьова прискорююча структура DTL. Поставлено завдання суміщення таких різнорідних прискорюючих структур в одному резонаторі.